Pengembangan Kurikulum Al-Islam Kemuhammadiyahan dan Bahasa Arab (ISMUBA) di SD Muhammadiyah Bendo Kulon Progo - Sri Lestari (Universitas Muhammadiyah Makassar, 2022)
Muhammadiyah Bendo Elementary School is one of Muhammadiyah's charitable efforts under the Muhammadiyah Regional Leadership of Kulon Progo Regency. In its implementation, applying the curriculum with reference to the National Curriculum and the Muhammadiyah Curriculum. The religious flagship program is part of the development of the ISMUBA curriculum, namely Tahsin Tahfidz Qur'an and Al-Qur'an Education Park (TPA). This program is fundamental to Kulon Progo Regent Regulation Number 65 of 2017 concerning Guidelines for Strengthening Character Education. The material for the Tahfidz Juz 30 program is based on the Tahfidz Al-Qur'an Syllabus in all districts of Kulon Progo. While the TPA material was developed by the Curriculum Development Team of SD Muhammadiyah Bendo.